PENGALAMAN KERJA, PELATIHAN KERJA, IKLIM OGANISASI DAN PENGARUHNYA TERHADAP KINERJA KARYAWAN PT. TRENGGINAS JAYA - jodi manihuruk; Erna Susilawati (Journal of Economics, Management, Business and Accounting (JEMBA), 2021)
Thiss study aims to determine work experience, job training, organizational climate, and its influence on employee performance at PT. Trengginas Jaya either partially or simultaneously. The sample used as many as 30 employees. This research uses descriptive and verification methods. Hypothesis testing techniques T-test and F-test and data analysis techniques for Multiple Linear Regression using SPSS v25 for Windowss software. The result of this study indicate that there is a significant effect of work experience, job training, and organizational climate on employee performance simultaneously of 26.907. In addition, work experience, job training, and organizational climate also partially have a significant effect on employe performance. Among these variables, partially Work Experience has a significantly greater level than the other three variables, which is 3.778